Natural Product Ginsenoside 20(S)-25-Methoxyl-Dammarane-3β, 12β, 20-Triol in Cancer Treatment: A Review of the Pharmacological Mechanisms and Pharmacokinetics - Kim, Dohyun; Park, Minwoo; Haleem, Iqra; Lee, Younghong; Koo, Jain; Na, Young Chae; Song, Gidong; Lee, Jaehwi (Frontiers in Pharmacology, 2020)
Panax ginseng has been used as an herbal medicine for thousands of years. Most of its pharmacological effects are attributed to its constituent ginsenosides, including 20(S)-25-methoxyl-dammarane-3β, 12β, 20-triol (20(S)-25-OCH3-PPD), which is one of the protopanaxadiol type ginsenosides. It has been found to exhibit anticancer effects by interacting with multiple pharmacological pathways, such as the Wnt/β-catenin, MDM2, ERK/MAPK, and STAT3 signaling pathways. However, its therapeutic potential could be limited by its low bioavailability mainly due to its low aqueous solubility. Thus, several studies have been conducted on its pharmacokinetics and its delivery systems, so as to increase its oral bioavailability. In this review, comprehensive information on its varying pharmacological pathways in cancer, as well as its pharmacokinetic behavior and pharmaceutical strategies, is provided. This information would be useful in the understanding of its diverse mechanisms and pharmacokinetics as an anticancer drug, leading to the design of superior 20(S)-25-OCH3-PPD-containing formulations that maximize its therapeutic potential.